MARKET BASE ANALYSIS IN DROPSHIP BUSINESS WITH APRIORI ALGORITHM IN DETERMINING R-BASED PRODUCT BUNDLING - Fauziyyah, Anni Karimatul (Indonesian Journal of Business Intelligence (IJUBI), 2019)
The association method will associate data using a priori (experience) rules that meet the minimum support requirements, namely the combination of each item in the database and the minimum confidence requirement, namely the strength of the relationship between items in the association rules. In this study, the sales transaction data for three months will be analyzed from the dropshipper in the field of sales of beauty and fashion products using the association method with a priori algorithm to look for product bundling data patterns. The minimum value of support is 10% and 20% confidence, and with % ain function where Ordinary Shampoo items become the main products in product bundling, obtained 15 packages of the strongest products with lift values more than 1.1.